Peran Viral Marketing Dan Kepercayaan Konsumen Terhadap Keputusan Pembelian - Rizky Anugerah Pratama; Kokom Komariah; Dicky Jhoansyah (Institut Penelitian Matematika, Komputer, Keperawatan, Pendidikan dan Ekonomi (IPM2KPE), 2022)
The purpose of this study was to analyze viral marketing and consumer confidence in purchasing decisions. The research method used are descriptive and associative research methods. Data collection techniques used are observation, interviews, questionnaires, documentation, and literature study. The data analysis technique starts from data compilation, data tabulation to the testing stage, namely using multiple correlation coefficients, coefficients of determination, multiple linear regression, simultaneous hypothesis testing (F test) and partial hypothesis testing (T test). Based on the results obtained, the study showed a positive and significant effect. The results of the f test showed that the independent variables, namely viral marketing and consumer trust, had a positive and significant influence together on the dependent variable, namely purchasing decisions. With a value of Fcount 43,452 > Ftable 1.65. While the results of the coefficient of determination of 0.570 which means that the influence of viral marketing and consumer trust on purchasing decisions is 57% while the remaining 43% is influenced by other factors not examined. The t-test results show that the viral marketing variable has a Tcount of 8.687 > Ttable 1.65 with a significant value of 0.000 <0.05, which means that there is a positive and significant influence between viral marketing on purchasing decisions. Then the consumer confidence variable has a Tcount of 6.589> 1.65 with a significant value of 0.000 <0.05, which means that there is a positive and significant influence between consumer confidence on purchasing decisions. Keywords: Viral Marketing, Consumer Trust, Purchase Decision